(Des)encontros de gerações no século XXI : experiências de crianças e adultos com as mídias e as novas tecnologias na cultura contemporânea - Ferrarini, Anabela Rute Kohlmann (2013)
In this research, I seek to conduct a study about contemporary childhood and experiences of children and adults with the media and new technologies in an intergenerational perspective. The concern of adults about new configurations that take on the childhood experiences of symbolic references offered to children, especially by the medias, and the possibility of easy access to new technologies, demands a need for research on the topic. Thus, I hope to contribute to the debate on the setting of childhood and adulthood in the contemporary world, stimulating a reflection that might lead to a better understanding of childhood in order to subsidize the adult in the task of educating then. Children star in experiments that prove knowledge and skills in their relations with the media-technological world, destabilizing our images of childhood, these images produced and signed historic, socially and culturally. Thus, from an intergenerational perspective, this research aims to analyze what adults and children say about their experiences with the media and new technologies in contemporary culture. Investigate also the speeches about being a child and living in contemporary childhood, seeking, in this dialogue, understand the meanings attributed to this time of life for both those who live today - children - as for those who already lived - adults (mother and teacher). Field research is a qualitative one, has a character of intervention takes place in the Escola Estadual Sagrado Coração de Jesus, in the city of Rondonopolis, Mato Grosso. Its locus is a class of 3rd year of elementary school, made up of children aged 8 and 9 years. The methodology I adopt is the participant observation of children in their school routine, and workshops for the questioning of the research topic, both with children and with adults. Perform, though, interviews and questionnaires, along with workshops and participant observation, resulting in grants in which I support - in dialogue with the theoretical foundations - in an attempt, after data organization, unravel the intricate relationship between adults, children, media and new technologies. As a means of recording, the workshops are filmed while interviews are audio recorded. It is noteworthy that the discourses produced by children and adults are analyzed based on the concepts of otherness and dialogism of Mikhail Bakhtin (1992, 1995), which comprises the discursive production from processes of dialogue and building values and social perspectives, arising contexts and different times, crossing the statements in their encounters and confrontations.